Peritoneal malignant mesothelioma (PMM), and primary peritoneal serous carcinoma (PPSC) and reactive mesothelial hyperplasia (RMH) of the peritoneum. Immunohistochemical and fluorescence in situ hybridisation (FISH) analyses. Issue 8 (4th January 2016) - Kawai, Toshiaki; Tominaga, Susumu; Hiroi, Sadayuki; Ogata, Sho; Nakanishi, Kuniaki; Kawahara, Kunimitsu; Sonobe, Hiroshi; Hiroshima, Kenzo
Abstract : Aims: Peritoneal malignant mesothelioma (PMM) is an uncommon tumour, accounting for only 7–9% of all mesotheliomas in Japan. Differential diagnosis between PMM and primary peritoneal serous carcinoma (PPSC), a high-grade serous carcinoma, may be difficult, and separating reactive mesothelial hyperplasia (RMH) from PMM can be even more challenging. Methods: To help differentiate PMM from PPSC and RMH, we used immunohistochemistry to examine mesothelial-associated markers (calretinin, AE1/AE3, CK5/6, CAM5.2, D2-40, WT-1, HBME1, thrombomodulin), adenocarcinoma-associated markers (CEA, BerEP4, MOC31, ER (estrogen receptor), PgR, TTF-1, Claudin-4, Pax8), and malignant-related and benign-related markers (epithelial membrane antigen (EMA), desmin, GLUT-1, CD146 and IMP3), and FISH to examine for homozygous deletion of 9p21. We used formalin-fixed, paraffin-embedded blocks from 22 PMMs (M:F=18:4; subtypes: 16 epithelioid, 6 biphasic), 11 PPSCs and 23 RMHs. Results: Seventeen of the mesotheliomas (four PMM from women) were classified as diffuse, while five were localised. Calretinin was 91% positive in PMM, but negative in PPSC (specificity, 100%). BerEP4, Claudin-4 and PAX8 were all 100% positive in PPSC (specificities, 100%, 95% and 95%, respectively, for excluding PMM). For distinguishing PMM and RMH, sensitivity for EMA in mesothelioma was 68%, while for IMP3 and GLUT-1 it was 64% and 50%, respectively, all with high specificities. FISH analysis revealed homozygous deletion of the 9p21 locus in 11/13 PMMs, but in 0/11 RMHs. Conclusions: Calretinin and BerEP4 may be the best positive markers for differentiating PMM from PPSC. EMA, in combination with IMP3 and desmin, is useful, and homozygous deletion of 9p21 may be helpful, for differentiating PMM from RMH.